2020
DOI: 10.5458/jag.jag.jag-2020_0006
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Anti-Proliferative Activity of Rare Aldohexoses against MOLT-4F and DU-145 Human Cancer Cell Line and Structure-Activity Relationship of D-Idose

Abstract: D-Allose (D-All), a C-3 epimer of D-glucose (D-Glc), is a naturally rare monosaccharide, which shows anti-proliferative activity against several human cancer cell lines. Unlike conventional anticancer drugs, D-All targets glucose metabolism and is non-toxic to normal cells. Therefore, it has attracted attention as a unique “seed” compound for anticancer agents. However, the anti-proliferative activities of the other rare aldohexoses have not been examined yet. In this study, we evaluated the anti-proliferative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…A study showed a rare sugar, D-Allose, possess anticancer effects [47,48,49,50,51] . It was also reported to have antiproliferative activity against MOLT-4F and DU-145 human cancer cell line [52] . Recently, 1H-Cycloprop[e]azulen-7-ol, decahydro-1, 1, 7-trimethyl-4-methylene-, [1ar-(1a.alpha.…”
Section: Discussionmentioning
confidence: 96%
“…A study showed a rare sugar, D-Allose, possess anticancer effects [47,48,49,50,51] . It was also reported to have antiproliferative activity against MOLT-4F and DU-145 human cancer cell line [52] . Recently, 1H-Cycloprop[e]azulen-7-ol, decahydro-1, 1, 7-trimethyl-4-methylene-, [1ar-(1a.alpha.…”
Section: Discussionmentioning
confidence: 96%
“…The biological relevance of idosides is further highlighted by the identification of 6-deoxy- l -idose in labdane-type diterpenes produced by Aster spathulifolius Caenorhabditis elegans, whereas d -idose was shown to exert an antiproliferative activity against leukemia cell lines . Moreover, l - glycero - d - ido -heptoses and 6-deoxy- d - ido -heptoses are found in the capsular polysaccharide (CPS) of Campylobacter jejuni HS:3 , and HS:4c, , respectively.…”
Section: Introductionmentioning
confidence: 99%
“…9 L-idose was also studied for its inhibitory effect against the growth of Caenorhabditis elegans, 10 whereas Didose was shown to exert an antiproliferative activity against leukemia cell lines. 11 Moreover, L-glycero-D-ido-heptoses and 6deoxy-D-ido-heptoses are found in the capsular polysaccharide (CPS) of Campylobacter jejuni HS:3 12,13 and HS:4c, 14,15 respectively.…”
Section: ■ Introductionmentioning
confidence: 99%
See 2 more Smart Citations